Evaluating The Role Of Climate On Dengue And Chikungunya Outbreaks And Transmission In Jaipur - Sita Ram Jat; Dr. Garima Sharma (Journal of Advanced Zoology, 2024)
The transmission of infectious illnesses, including dengue and chikungunya fevers, is accelerated by climate change. The Kimakonde language is where the word "chikungunya" means "to dry up or become contorted." One arthropod-borne virus disease that has been documented since 1824 is chikungunya fever (CHIKF). There have been 4,086 confirmed cases of dengue fever in the Jaipur districts alone, accounting for 32% of the state’s overall dengue cases. The probability of infectious diseases, particularly those carried by vectors, is expected to rise as a result of global warming since more extreme precipitation episodes are anticipated. Illness management requires public health initiatives and ongoing monitoring. The frequency of dengue and chikungunya fever in Jaipur, India, was investigated in this study. Descriptive statistics were used to synthesize the data retrieved from various sources, including government databases, monitoring programmes, and hospital records. We used correlation analysis for 104 samples to look for links between weather and the incidence of Dengue and Chikungunya. There is a robust positive association between temperature and chikungunya cases, demonstrating that climate plays a substantial role in disease transmission. When developing therapies for vector-borne diseases, it is crucial to take demographic variables, environmental factors, and disease incidence patterns into account, as shown in this study. Understanding and managing these disorders requires a comprehensive strategy. It is essential to monitor patients continuously for improved treatment and prevention.